Curious Intersections, Uncommon Magic: Steve Reich’s It’s Gonna Rain - Scherzinger, Martin (Current Musicology, 2005)
1965 was a watershed year in the life of Steve Reich. Following numerous experiments with magnetic tape, he had, while creating his tape piece It’s Gonna Rain, identified a fascinating process that would serve as the basic compositional tool of his output until about 1971, and as a foundational component of his output thereafter. Reich’s preoccupation with processoriented music in turn helped define a musical trend that shifted the standard historical narrative of twentieth -century concert music away from the reigning high modernist serialism of the 1950s toward minimalism. Defenders of the new style emphasize the cultural triumph of minimalism. For Susan McClary, minimalism is “perhaps the single most viable extant strand of the Western art-music tradition;” for K. Robert Schwarz, a specialist in this style, minimalism is “a potent force … its influence is pervasive and enduring;” and for the composer John Adams, minimalism is “the only really interesting, important stylistic development in the past 30 years” (McClary 2004:289-98; Schwarz 1997:1-17; Adams quoted in Schwarz 1996a:177). These writers often attend to minimalism’s programmatic reaction to the perceived structural complexities of high modernism with its ametric rhythms and pervasive intervallic dissonances. In contrast to high modernism, minimalism offered musical structures dearly audible to the listener; its rhythms were pulse-based, often elaborated in the context of extended repetition of short musical figures, and its pitch structures were simple, usually associated with, though not identical to, traditional diatonic constellations. Commentators may differ on the relationship minimalism takes to modernism-McClary argues in terms of a qualified Oedipal “reaction formation” to modernism; Wim Mertens argues in terms of a negative dialectical “final stage” of high modernism-but few commentators fail to situate high modernism as the central referent in describing the emergence of minimalism in music (McClary 2004:292; Mertens 2004:308). Whether the argument hinges on a theory of history beholden to Freud or one beholden to Hegel, modernism under these readings remains minimalism’s basic condition of possibility.